Analysis Of The Effect Of Promotion On Return Visits Of Outpatient Patients At Batara Guru Regional Hospital - Kasriana, Kasriana; Anwar Ramli; Faiz Satrianegara (Sean Institute, 2024)
his study aims to analyze the influence of promotion on outpatient visit interest at Batara Guru Hospital. This type of research is a quantitative approach with a cross-sectional design to determine the relationship between independent variables (promotion) and dependent variables (patient visits) with data collection carried out simultaneously. The frequency of promotion at Batara Guru Hospital, most respondents stated that it was good, namely 69 respondents (79.3%), while 18 respondents (20.7%) stated that it was not good. The frequency of outpatient visit interest at Batara Guru Hospital, most respondents stated that they were interested, namely 70 respondents (80.5%), while 17 respondents (19.5%) stated that they were not interested. It can be seen that the t-value of 2.298 is greater than the t-table value of 1.663 with a significance value of 0.02 t-table and the Significant value.